A comprehensive generic‐level phylogeny of the sunflower family: Implications for the systematics of Chinese Asteraceae. Issue 4 (July 2016) - Fu, Zhi‐Xi; Jiao, Bo‐Han; Nie, Bao; Zhang, Guo‐Jin; Gao, Tian‐Gang; ,
Abstract: The sunflower family (Asteraceae) is the largest and the most diverse flowering plant family, comprising 24 000–30 000 species and 1600–1700 genera. In China, Asteraceae are also the largest family, with approximately 2336 indigenous species in 248 genera. In the past two decades, molecular phylogenetic analyses has contributed greatly to our understanding of the systematics of Asteraceae. Nevertheless, the large‐scale analyses and knowledge about the relationships of Chinese Asteraceae at the generic level as a whole are far from complete due to difficulties in sampling. In this study, we presented a three‐marker ( rbcL, ndhF, and matK ) phylogeny of Asteraceae, including 506 genera (i.e., approximately one‐third of Asteraceae genera). The study sampled 200 Chinese genera (i.e., approximately 80% of Chinese Asteraceae genera). The backbones of the new phylogeny were largely congruent with earlier studies, with 13 subfamilies and 45 tribes recognized. Chinese Asteraceae were distributed in 7 subfamilies (Mutisioideae, Wunderlichioideae, Carduoideae, Pertyoideae, Gymnarrhenoideae, Cichorioideae, and Asteroideae) and 22 tribes (Mutiseae, Hyalideae, Cardueae, Pertyeae, Gymnarrheneae, Vernonieae, Cichorieae, Doroniceae, Senecioneae, Astereae, Anthemideae, Gnaphalieae, Calenduleae, Inuleae, Athroismeae, Helenieae, Coreopsideae, Neurolaeneae, Tageteae, Millieae, Eupatorieae, and Heliantheae). Chinese Asteraceae lacked 6 basal subfamilies and 23 tribes. Several previously ambiguous relationships were clarified. Our analyses also resolved some unplaced genera within Chinese Asteraceae. Finally, our phylogenetic tree was used to revise the classification for all genera of Chinese Asteraceae. In total, 255 genera, 22 tribes, and 7 subfamilies in China are recognized.